Praktik dan Implikasi Perkawinan Bawah Tangan Terhadap Tujuan Keluarga Perspektif Maqasid Al-Usrah - Chodir, Fatkul; Aspandi, Aspandi (Indonesian Journal of Humanities and Social Sciences, 2023)
The escalating prevalence of unregistered marriages in Indonesia has prompted this research, highlighting its ramifications across diverse facets of family objectives. This study seeks to dissect the repercussions of unregistered marriages on family goals, employing the theoretical lens of Maqasid al-Usrah by Jamaluddin 'Athiyah. Employing a normative juridical approach, the research scrutinizes Indonesian marriage law and jurisprudential literature as primary legal sources. The literature study method is utilized, with primary data derived from jurisprudence books and Islamic law documents pertinent to the research theme, while secondary data encompasses research findings, journals, and related documents. The findings underscore that unregistered marriages pose formidable challenges to legal certainty guarantees concerning various dimensions of family goals, encapsulating seven key aspects. The study's implications stress the imperative of reinforcing regulations mandating marriage registration as a means to protect and ensure the realization of family goals. This research contributes valuable insights to the ongoing discourse on the legal and societal consequences of unregistered marriages, paving the way for informed policy recommendations and potential amendments to existing legal frameworks.